Analisis Faktor-faktor yang Mempengaruhi Kinerja Rantai Pasokan pada Industri Manufaktur Skala Kecil dan Menengah di Jawa Timur - Ellitan, Lena (Kajian Manajemen dan Bisnis, 2010)
This research conducted to investigate the influence factors (environment factors, intra-organizational facilitator, and inter-organizational factors) of information sharing and information quality and its effect on operational performance of supply chain. Data are collected through mailed questionnaire to 500 top management of small and medium entreprises in East Java Province, Indonesia.